PENGGUNAAN METODE EKSPERIMEN PENCAMPURAN WARNA UNTUK MENINGKATKAN KONSENTRASI ANAK PADA KELOMPOK B DI TK CIPTA INSANI SIDOARJO - Sari, Amalia Prastika; Virdaus, Varia Virdania (MOTORIC, 2025)
This research was motivated by the students' lack of ability to concentrate. The aim of this research is to determine how to increase children's concentration through color mixing experimental activities. This type of research uses classroom action research (PTK). The research subjects were group B students at Cipta Insani Sidoarjo Kindergarten. Data collection used observation and documentation. The research was carried out in II cycles. The results of the research showed that the students' concentration increased with each cycle. In Cycle I, the results of the assessment using the BSB criteria for the first indicator reached 54.5%, for the second indicator it reached 63.3% and for the third indicator it reached 54.5%. In Cycle II, the results of the assessment using the BSB criteria for the first indicator reached 90.9%, for the second indicator it reached 81.8% and for the third indicator it reached 81.9%. Keywords: Concentration, Experiment, Color Mixing